2019
DOI: 10.1523/eneuro.0439-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Prodromes and Preclinical Detection of Brain Diseases: Surveying the Ethical Landscape of Predicting Brain Health

Abstract: The future of medicine lies not primarily in cures but in disease modification and prevention. While the science of preclinical detection is young, it is moving rapidly. Preclinical interventions offer hope to decrease the severity of a disease or delay the development of a disorder. With such promise, the research and practice of detecting brain disorders at a preclinical stage present unique ethical challenges that must be addressed to ensure the benefit of these technologies. Direct brain interventions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 97 publications
(101 reference statements)
0
52
0
Order By: Relevance
“…Many discussed the difficulty to discern normal aging from latent AD [14-16, 18, 20, 22, 25, 26, 28-30, 32, 33, 35], as the majority of cognitively healthy elderly with abnormal biomarkers never develop dementia [14-16, 20-23, 25, 26, 28-30, 32, 33, 36], since AD is multi-factorial [16, 18, 25, 26, 30, 34]. It was argued that procedures are not without burden or risk [14, 16, 18, 20, 21, 23, 24, 33] and consequences of incorrectly labeling people as ‘patients in waiting’ [24, 33] could be severe [14, 16, 24-27, 30]. Most authors concluded that biomarker criteria require final demonstration of validity in populations without dementia [14-23, 25, 26, 29, 30, 32-34, 37].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many discussed the difficulty to discern normal aging from latent AD [14-16, 18, 20, 22, 25, 26, 28-30, 32, 33, 35], as the majority of cognitively healthy elderly with abnormal biomarkers never develop dementia [14-16, 20-23, 25, 26, 28-30, 32, 33, 36], since AD is multi-factorial [16, 18, 25, 26, 30, 34]. It was argued that procedures are not without burden or risk [14, 16, 18, 20, 21, 23, 24, 33] and consequences of incorrectly labeling people as ‘patients in waiting’ [24, 33] could be severe [14, 16, 24-27, 30]. Most authors concluded that biomarker criteria require final demonstration of validity in populations without dementia [14-23, 25, 26, 29, 30, 32-34, 37].…”
Section: Resultsmentioning
confidence: 99%
“…Clinical utility was contested, mainly due to the absence of a disease-modifying therapy [14-16, 18, 20, 21, 23, 24, 26, 27, 30, 33, 34, 36, 38], and limited effectiveness of symptom suppressing medications, which has not been demonstrated in predementia stages of AD [21, 24]. On the other hand, several authors suggested lifestyle interventions could delay cognitive impairment [14, 16, 17, 21-31, 33], although evidence on their effectiveness remains inconclusive [14, 15, 21, 30], and according to some, such health improvements should be pursued regardless of one’s biomarker status [16, 23, 30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations